Scaling and root planning and locally delivered minocycline could reduce the load of Prevotella intermedia in an interdependent pattern, which correlated with symptomatic improvements of chronic periodontitis: a short-term randomized clinical trial - Deng S; Wang Y; Sun W; Chen H; Wu G (Dove Medical Press, 2015)
Shuli Deng,1 Ying Wang,1 Wei Sun,1 Hui Chen,1 Gang Wu2 1Department of Conservative Dentistry, Affiliated Hospital of Stomatology, Medical College, Zhejiang University, Hangzhou, People’s Republic of China; 2Department of Oral Implantology and Prosthetic Dentistry, Academic Centre for Dentistry Amsterdam (ACTA), VU University Amsterdam and University of Amsterdam, MOVE Research Institute Amsterdam, Amsterdam, the Netherlands Background: To evaluate the respective or combinatory efficacy of locally delivered 2% minocycline (MO) and scaling and root planning (SRP) by assessing both clinical parameters and the loads of four main periodontal pathogens in treating chronic periodontitis (CP).Methods: Seventy adults with CP were randomly assigned to the three treatment groups: 1) SRP alone; 2) MO alone; and 3) combinatory use of SRP and MO (SRP + MO). Before and 7 days after the treatments, we evaluated both clinical parameters (pocket depth [PD] and sulcus bleeding index [SBI]) and the gene load of four main periodontal pathogens (Aggregatibacter actinomycetemcomitans [Aa], Fusobacterium nucleatum [Fn], Porphyromonas gingivalis [Pg], and Prevotella intermedia [Pi]).Results: The bacterial prevalence per patient was Aa, 31.25%; Fn, 100%; Pg, 95.31%; and Pi, 98.44%. Seven days after treatments, the three treatments could significantly reduce both PD and SBI, but not detection frequencies of the four pathogens. For PD, the reduction efficacy of SRP + MO was significantly higher than that of both MO and SRP. Only Pg responded significantly to SRP. Pg and Fn could be significantly reduced in the presence of MO. Only SRP + MO but not the respective showed a significant reduction effect on the gene load of Pi. The reduction of PD significantly correlated with the gene load of Pi (r=0.26; P=0.042) but not of the other bacteria.Conclusion: SRP and MO could reduce the load of Pi in an interdependent pattern, which correlated with symptomatic improvements of CP.Keywords: chronic periodontitis, minocycline, scaling and root planning, pocket depth, sulcus bleeding index, Prevotella intermedia